Evolution and Religion in American Education - Long, David E. author. aut Link
XIV, 190 p.
Keywords: Evolution and Religion in American Education shines a light into one of America’s dark educational corners, exposing the regressive pedagogy that can invade science classrooms when school boards and state overseers take their eyes off the ball. It sets out to examine the development of college students’ attitudes towards biological evolution through their lives. The fascinating insights provided by interviewing students about their world views adds up to a compelling case for additional scrutiny of the way young people’s educational experiences unfold as they consider—and indeed in some cases reject—one of science’s strongest and most cogent theoretical constructs. Inevitably, open discussion and consideration of the theory of evolution can chip away at the mental framework constructed by Creationists, eroding the foundations of their faith. The conceptual battleground is so fraught with logical challenges to Creationist dogma that in a number of cases students’ exposure to such dangerous ideas is actively prevented. This book provides a detailed map of this astonishing struggle in today’s America—a struggle many had thought was done and dusted with the onset of the Enlightenment.